Prevalence of Antibiotic-Resistant Salmonella enterica Isolates from Ready-to-Eat Meat (Suya) and its Contact Surfaces in Minna Metropolis, Nigeria - Rejoice Ekli; Jeremiah David Bala; Salamatu Machunga-Mambula; Frederick Adzitey; Helen Shnada Auta; Hadiza Lami Muhammad; Hussaini Anthony Makun (Food Safety and Risk)
Abstract This study evaluated microbial contamination, antibiotic resistance of Salmonella enterica and hygienic practices associated with ready-to-eat (RTE) meat (suya) in Minna Metropolis, Niger State, Nigeria. Three hundred and eighty-four (384) samples (suya meat, spices, knives, and vendor hands) were analyzed for microbial contamination and the presence of Salmonella enterica according to Bacteriological Analytical Manual of the U.S. Food and Drug Administration. Antibiotic resistance for Salmonella isolates was determined using the disk diffusion method. Vendor hygiene practices were assessed via questionnaires. The results revealed that microbial load ranged from 8.5 × 10⁷ to 2.35 × 10⁸ cfu/g or cfu/cm2 across all study locations, with the lowest from knives sampled at Tunga and highest from hand samples in Maikunkele. The overall prevalence of Salmonella enterica was 13%, with the lowest in spices and hand samples (9% each) and highest in suya meat (26%). The Salmonella enterica were highly resistant to amoxicillin (65%) and susceptible to trimethoprim-sulfamethoxazole (95%). Multidrug resistance was 43.1%. Resistant to amoxicillin was the commonest and was exhibited by 9 Salmonella enterica isolate. There was limited formal education (56.0%) and occupational training (51.3%) among suya vendors with poor adherence to hygienic practices. Training of suya vendors on hygienic handling of RTE meats is recommended.